Gender, Race, and the Regulation of Native Identity in Canada and the United States: An Overview - Lawrence, Bonita (Hypatia, 2003)
The regulation of Native identity has been central to the colonization process in both Canada and the United States. Systems of classification and control enable settler governments to define who is “Indian,” and control access to Native land. These regulatory systems have forcibly supplanted traditional Indigenous ways of identifying the self in relation to land and community, functioning discursively to naturalize colonial worldviews. Decolonization, then, must involve deconstructing and reshaping how we understand Indigenous identity.